The Protective Effects of Crocetin on Aβ1-42-Induced Toxicity in Ht22 Cells - Kong, Yan; Kong, Ling-Ping; Luo, Tao; Li, Guang-Wu; Jiang, Wei; Li, Sheng; Zhou, Yue; Wang, Hua-Qiao (CNS & Neurological Disorders - Drug Targets, 2014)
Alzheimer's disease (AD) is a neurodegenerative disorder characterized by selective neuron loss, amyloid plaques, and neurofibrillary tangles. Oxidative stress plays an essential role in the progression of AD. As the carotenoid crocetin has been shown to possess anti-oxidative effects in previous studies, now we have investigated the neuroprotective effects and potential molecular mechanism of crocetin action against Aβ1-42 induced toxicity in mouse hippocampal-derived Ht22 cells. Our results showed that there was a significant reduction in Ht22 cell viability when exposed to Aβ1-42 (0.5 µM) for 24 hours. Furthermore, increased reactive oxygen species production, reduced mitochondrial membrane potential and phosphorylation of extracellular signal-regulated kinase were observed in the cells. However, when pre-incubated with crocetin (1 and 5 µM) for 24 hours followed by Aβ1-42 (0.5 µM) challenge, there was a marked increase in cell viability, reduced in reactive oxygen species formation, and increased mitochondrial membrane potential. Pre-treatment with crocetin (5 µM) also activated extracellular signal-regulated kinase 1/2 phosphorylation. These data demonstrate that crocetin has neuroprotective effects on Aβ1-42-induced Ht22 cell injury which may result from its anti-oxidative role. This finding may provide a potential therapeutic candidate for the treatment of AD.
Keywords: Ht22